1998
DOI: 10.2337/diabetes.47.12.1935
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mRNAs encoding uncoupling proteins in human skeletal muscle: effects of obesity and diabetes.

Abstract: To explore the potential role of the uncoupling protein (UCP) family in human obesity and diabetes, we have used the reverse transcription-polymerase chain reaction to quantify UCP mRNA expression in human skeletal muscle. Levels of mRNA for UCP2, and for both short (UCP3S) and long (UCP3L) forms of UCP3, were highly correlated in individuals, indicating that gene transcription of these UCPs may be coordinately regulated by common mechanisms. In normal glucose-tolerant individuals, muscle UCP2 mRNA levels were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
3
4

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 0 publications
6
60
3
4
Order By: Relevance
“…The results of this study are in agreement with the previously observed relationship between plasma leptin levels and UCP3 mRNA levels in skeletal muscle. Note that we did not find a relationship between UCP3 mRNA expression and body fat percentage in this study; however, Bao et al (2) have shown a positive correlation of skeletal muscle UCP3 mRNA with body fat percentage and BMI in nondiabetic individuals. A potential explanation for the absence of this relationship within the current data is that this sample is relatively lean.…”
Section: Discussioncontrasting
confidence: 51%
“…The results of this study are in agreement with the previously observed relationship between plasma leptin levels and UCP3 mRNA levels in skeletal muscle. Note that we did not find a relationship between UCP3 mRNA expression and body fat percentage in this study; however, Bao et al (2) have shown a positive correlation of skeletal muscle UCP3 mRNA with body fat percentage and BMI in nondiabetic individuals. A potential explanation for the absence of this relationship within the current data is that this sample is relatively lean.…”
Section: Discussioncontrasting
confidence: 51%
“…Suggested alternative functions include the regulation of lipid (especially FFA) metabolism, as various situations that raise circulating levels of FFA increase both UCP-2 and -3 expression in white fat and skeletal muscle (Boss et al, 2000). These conditions include fasting, high-fat feeding and intralipid infusion in rodents (Boss et al, 1997a;Fleury et al, 1997;Matsuda et al, 1997;Weigle et al, 1998) and obesity, type-2 diabetes and intralipid infusion in man (Millet et al, 1997;Bao et al, 1999;Khalfallah et al, 2000;Nisoli et al, 2000). Moreover, in vitro, FFA up-regulate UCP-2 in pre-adipocytes and hepatocytes, and UCP-3 in muscle cells (Samec et al, 1998b;Cortez-Pinto et al, 1999;Reilly and Thompson, 2000).…”
mentioning
confidence: 99%
“…Type II diabetes mellitus is associated with hypertriglyceridaemia, hypercholesterolaemia and increased NEFA in plasma. As noted above, UCP2 expression in skeletal muscle of human diabetic patients is increased [97,100]. In fa/fa rat muscle, no difference [144] or a decrease in expression is reported [89].…”
Section: Relation Of Ucp2 With Metabolic Diseasesmentioning
confidence: 70%
“…In contrast, patients with Type II (non-insulin-dependent) diabetes mellitus show increased UCP2 mRNA in the vastus lateralis muscle, a primarily oxidative-type tissue [97,100]. While fasting in both lean and non-diabetic obese subjects results in an increased UCP2 gene expression [17,100] no change is observed in diabetic patients [100].…”
Section: Fuel Metabolismmentioning
confidence: 99%